Development of The Application "Kita Sarjana" To Support The Academic Process of Final-Year Students at Universitas Negeri Makassar - Akbar, Muh.; Agusnaya, Nurrahmah; Nirmala, Putri; Ilmah, Nurul (ARRUS Journal of Social Sciences and Humanities, 2024)
The development of information and communication technology has significantly impacted higher education, including at Universitas Negeri Makassar. Students often face administrative and communication challenges during their academic journey, particularly from the proposal stage to graduation. To address these issues, the "Kita Sarjana" application was developed as an integrated digital solution. This application facilitates various academic needs, including mentoring management, document submission, registration, and financial information management. The research utilized the waterfall development model, involving analysis, design, implementation, testing, and maintenance phases. The results indicate that the application successfully enhances the efficiency of academic processes and provides a better user experience through an intuitive interface design. Thus, the "Kita Sarjana" application represents a critical innovation in supporting a digitally-driven higher education ecosystem.